THE GEOGRAPHY OF AUGUSTUS BETWEEN PERSISTENCE AND EVOLUTIONARY DYNAMICS - Simone Bozzato; Giacomo Bandiera (Bollettino della Società Geografica Italiana)
This article proposes a reflection on the Augustan territorial reordering action, interpreted through a unifying paradigm, the flexible pragmatism. Pragmatism, in reading the morphological differences and socio-economic dynamics existing in the Italian communities and flexibility, to put this diversity in a homogeneous picture of territorial-administrative structure, with generalized and generalizing characters. In the Campi Flegrei, a restricted geographical scope, with morphological diversities and an organic distributions of economic, social and military actions, Augustus does partition and chooses very different administrative powers, applying this flexible pragmatism. Today a different development and new territorial dynamics are speculated for the entire area flegrea, based on a strategic reopening of the city to the sea and on the enhancement of persistences of morphological and geographical-cultural character. The Augustan example, his pragmatism, should be reapplied proceeding, in reverse, to an administrative unification of the whole area flegrea, with a general and unifying approach to government. Functional differentiations choises should be taken again in different places, consistent with the Genius loci and connected between them, able to support each other in a process of general territorial changes and consistent with a contemporary, place and systemic relief. These new regionalization processes are common to many Italian coastal areas, with the same dynamics and the same territorial resilience, recorded as an intrinsic possibility of the places, absorbed the state of perturbation as the use of the territory not consistent with its core values, to become again potential areas of new territorial processes, in harmony with the values and the geographical landscape and cultural milieu that characterizes them.